2014
DOI: 10.2527/jas.2014-8272
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of slice characteristics and sensory characteristics of bacon from immunologically castrated barrows with bacon from physically castrated barrows, boars, and gilts

Abstract: The objectives were to compare slice characteristics and sensory attributes of bacon from immunologically castrated (IC) barrows with bacon from other sexes using a trained sensory panel. Bacon was obtained for sensory evaluation from 3 experiments. In Exp. 1, trimmed and squared bellies (n=180) of IC barrows, IC barrows fed ractopamine hydrochloride (IC+RAC), physically castrated (PC) barrows, intact males (IM), and gilts were used. Data were analyzed as a general linear mixed model and pen (n=48) served as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…In addition, bacon from IC has been shown to exhibit higher levels of lipid oxidation, but only after long storage times (when frozen for 12 weeks), whereas the oxidation did not exceed sensory thresholds neither it affected normal product shelf life [ 128 ]. Results of the trials on prolonging of the V2-SL interval from 5 to 7 weeks concluded that this management procedure mainly eliminates differences in external appearance (i.e., fatness/leanness), slicing loss and slice cohesion in comparison to SC and may be enough to significantly improve bacon quality [ 123 , 129 ].…”
Section: Meat Product Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bacon from IC has been shown to exhibit higher levels of lipid oxidation, but only after long storage times (when frozen for 12 weeks), whereas the oxidation did not exceed sensory thresholds neither it affected normal product shelf life [ 128 ]. Results of the trials on prolonging of the V2-SL interval from 5 to 7 weeks concluded that this management procedure mainly eliminates differences in external appearance (i.e., fatness/leanness), slicing loss and slice cohesion in comparison to SC and may be enough to significantly improve bacon quality [ 123 , 129 ].…”
Section: Meat Product Qualitymentioning
confidence: 99%
“…Adjustment of the delay between the second vaccination and slaughter (to over 7 weeks) may help in the modification of leanness/fatness of the product and to avoid negative consequences on processing and slicing yields [ 123 , 129 ].…”
Section: Figurementioning
confidence: 99%
“…Крім того, інші дослідники також акцентують увагу не тільки на больовій реакції за оперативного втручання, а й найменшій ефективності порівняно з імунологічною кастрацією (Little et. al., 2014), яка стала повноцінним альтернативним методом стерилізації кнурів (Zamaratskaia et al, 2015).…”
Section: обговоренняunclassified